INFLUENCE OF EMOTIONAL INTELLIGENCE AND SOCIAL SUPPORT ENTREPRENEURIAL ORIENTATION OF INCOMING STUDENTS TO THE AREA OF BUSINESS ADMINISTRATION NATIONAL UNIVERSITY OF PERU AND ECUADOR - Fairlie Frisancho, Ebor (2015)
ABSTRACT We carried out a longitudinal study describing the influence of EI and SS in the OE of students entering the university, that is, when you start your career in the Faculty, after the academic training, we will continue the investigation when students finish his career in 2017 between National Universities of Peru and Ecuador career management science. The objectives have been met as evidenced by the results of the study: A) Meet Entrepreneurial Orientation (EO), emotional intelligence (EI) and Social Support (SS) of students to enter the university; B) Discover the evolution of OE, IE and SS to graduate career; C) Find the relationship between OE and IE SS incoming students; and D) Establish comparisons OE, IE and SS according to demographic, such as sex, age and other data variables. Where they found significant relationships between these variables and most of all a similarity in entrepreneurial behavior of students in both countries. The survey has been taken 72 Peruvian students of Universidad Nacional Mayor de San Marcos (the most representative) and 233 of Ecuador including only 2 Universities Faculty of Administrative Sciences are the Universidad Península de Santa Elena and the Universidad Laica Eloy Alfaro de Manabí; in the future, it is proposed to extend the sample with cultural studies and relate to socioeconomic conditions or other educational levels.